THE ROLE OF KKN STUDENTS IN CARRYING OUT MALAY LANGUAGE TEACHING ACTIVITIES AT THE LOCATION OF SINGHANAKHON WITTAYANUSORN SCHOOL, THAILAND - Hurriyaturrohman, Hurriyaturrohman; Cantika, Melodia; Suharti, Titing; Sundarta, M. Imam; Ritzkal, Ritzkal (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Ibn Khaldun University Bogor International KKN is a form of community service activity. Real Work Lectures will be held on 16 May – 30 September 2023. Activities consist of teaching activities for junior high school students (Mattayom), and community service activities. This article discusses the school activities of Singhanakhon Wittayanusorn School and additional activities of KKN students. KKN activities aim to provide experience and as a form of learning process for students to explore the school's potential that can be developed. The learning method used is to use a basic Malay language book for the easiest introduction to vocabulary. An additional activity for KKN students is the Minicamp Qur'an activity which aims to teach students to create ash-syu'ur Al-Qur'ani (Qur'anic feelings) in students, instilling the spirit of increasing recitations of the Qur'an. The community service activities carried out include helping to clean the garden and planting mango tree seedlings in the garden of the school owner of the Singhanakhon Wittayanusorn School with the aim of creating a sense of care for the environment and a form of cooperation and mutual cooperation with the community. Ibn Khaldun University Bogor's KKN activities are expected to provide benefits to the community, students and schools, especially those aimed at creating a generation that can develop in languages ​​other than their own country and become role models in all things.